(untitled) (European Journal of Pure and Applied Mathematics, 2021)
In this note, first we add some new results in Gamma LA-rings and then we initiate the notion of Î“-LA-semirings. Moreover, we introduce and discuss the terms left ideals, right ideals, bi-ideal, quasi ideals, almost prime and weakly almost prime ideals of a Î“-LA-semiring and their characterizations.